Pengaruh Model Pembelajaran Hypnoteaching terhadap Kemampuan Menulis Cerpen Siswa Kelas XI SMAN 1 Cihara Tahun Pelajaran 2018/2019 - Saraswati, Saraswati; Yuliasari, Meli (Universitas Mathla'ul Anwar Banten, 2019)
This research aims to answer the formulation of question raised about whether there is an effect of Hypnoteaching learning model on short story writing ability of Class XI students of SMA Negeri 1 Cihara, 2018/2019 academic year. The method used in this research is experimental method conducted at SMA Negeri 1 Cihara, by taking students of class XI as population. The random results for the two existing classes obtained Class XI A as experimental class and class XIB as control class. Each class has 30 students, thus the number of samples in this research are 60 students. Class XIA gets treatment using Hypnoteaching learning model. Meanwhile, class XIB as control class using direct learning model (expository). Based on data analysis obtained that student’s short story writing ability of class XI SMA Negeri 1 Cihara, 2018/2019 academic year which uses Hypnoteaching learning model has good category with average value of 79,1. While, short story writing ability of students which uses direct learning model (expository) at class XIB has enough category with average value of 70,26. It means, there is a positive effect of Hypnoteaching learning model on short story writing ability of students at Class XI SMA Negeri 1 Cihara, 2018/2019 academic year. It can be seen from the result of hypothesis test using t-test with a significant level 0,05’ gained tcount 4,758 and ttable 1,6723; obtained tcount 4,758 ttable 1,6723, so is rejected and is accepted. In short, states that there is no effect of Hypnoteaching learning model on short story writing ability and states that there is an effect of Hypnoteaching learning model on short story writing ability, then is rejected and is accepted.